Gender Roles and Changes in Society (International Journal of Scientific Trends, 2025)
The article talks about the features and importance of strengthening the norms of gender equality in the Constitution of the Republic of Uzbekistan, the goal of developing a system of support for women and ensuring gender equality in the Uzbekistan 2030 strategy and laws. In addition, the article discusses the strengthening of norms guaranteeing gender equality in legislation, how this works in practice, as well as social factors that can negatively affect the implementation of gender policies pursued by the state.